Tìm x:
x^2 + 6x
x^2 - 25x + 250 = 0
x^2 + 9x = 10
2x^2 + 9x = 35
(x^2 - 2x - 1)^2 - 5 (x^2 - 2x - 1) - 14 = 0
(2k^2 + 5k + 1)^2 - 12 (2k^2 + 5k + 1) + 32 = 0
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
b) = (x^2)^2 + 18x^2 + 9^2 -18x^2
= (x^2 + 9) ^2 - 18x^2
= ( x^2 + 9 - 18x ) ( x^2 +9 + 18x)
Q(x).( x - 2 ) + 28 = ( x2 + x + 1 )( x + 2 )
⇔ Q(x).( x - 2 ) = x3 + 3x2 + 3x + 2 - 28
⇔ Q(x).( x - 2 ) = x3 + 3x2 + 3x - 26
⇔ Q(x).( x - 2 ) = x3 - 2x2 + 5x2 - 10x + 13x - 26
⇔ Q(x).( x - 2 ) = x2( x - 2 ) + 5x( x - 2 ) + 13( x - 2 )
⇔ Q(x).( x - 2 ) = ( x - 2 )( x2 + 5x + 13 )
⇔ Q(x) = x2 + 5x + 13
( 1 + x )3 - ( x - 2 )3 = x3 + 1
⇔ 1 + 3x + 3x2 + x3 - ( x3 - 6x2 + 12x - 8 ) = x3 + 1
⇔ 1 + 3x + 3x2 + x3 - x3 + 6x2 - 12x + 8 = x3 + 1
⇔ 9x2 - 9x + 9 = x3 + 1
⇔ x3 + 1 - 9x2 + 9x - 9 = 0
⇔ x3 - 9x2 + 9x - 8 = 0
⇔ x3 - 8x2 - x2 + 8x + x - 8 = 0
⇔ x2( x - 8 ) - x( x - 8 ) + ( x - 8 ) = 0
⇔ ( x - 8 )( x2 - x + 1 ) = 0
⇔ x - 8 = 0 hoặc x2 - x + 1 = 0
⇔ x = 8 [ do x2 - x + 1 = ( x2 - x + 1/4 ) + 3/4 = ( x - 1/2 ) + 3/4 ≥ 3/4 > 0 ∀ x ]
c) x2 + 9x = 10
x2 + 9x - 10 = 0
=> x2 - x + 10x - 10 = 0
=> x(x - 1) + 10(x - 1) = 0
=> (x + 10)(x - 1) = 0
=> \(\orbr{\begin{cases}x=-10\\x=1\end{cases}}\)
d) 2x2 + 9x = 35
=> 2x2 + 9x - 35 = 0
=> 2x2 + 14x - 5x - 35 = 0
=> 2x(x + 7) - 5(x + 7) = 0
=> (x + 7)(2x - 5) = 0
=> \(\orbr{\begin{cases}x=-7\\x=\frac{5}{3}\end{cases}}\)
(x2 - 2x - 1)2 - 5(x2 - 2x - 1) - 14 = 0
=> (x2 - 2x - 1)2 + 2(x2 - 2x - 1) - 7(x2 - 2x - 1) - 14 = 0
=> (x2 - 2x - 1)(x2 - 2x + 1) - 7(x2 - 2x + 1) = 0
=> (x2 - 2x + 1)(x2 - 2x - 8) = 0
=> (x - 1)2 (x - 4)(x + 2) = 0
=> x = 1 hoặc x = 4 hoặc x = -2
e) (2k2 + 5k + 1)2 - 12(2k2 + 5k + 1) + 32 = 0
=> (2k2 + 5x + 1)2 - 4(2k2 + 5k + 1) - 8(2k2 + 5k + 1) + 32 = 0
=> (2k2 + 5k + 1)(2k2 + 5k - 3) - 8(2k2 + 5k - 3) = 0
=> (2k2 + 5k - 3)(2k2 + 5k - 7) = 0
=> (2k2 + 6k - k - 3)(2k2 - 2x + 7k - 7) = 0
=> (k + 3)(2k - 1)(k - 1)(2k + 7) = 0
=> k = -3 hoặc k = 1/2 hoặc k = 1 hoặc k = -7/2
1.x2 + 6x = 0 < như này nhỉ ? >
⇔ x( x + 6 ) = 0
⇔ x = 0 hoặc x + 6 = 0
⇔ x = 0 hoặc x = -6
2. x2 - 25x + 250 = 0
⇔ ( x2 - 25x + 625/4 ) + 375/4 = 0
⇔ ( x - 25/2 )2 = -375/4 ( vô lí )
=> Phương trình vô nghiệm
3. x2 + 9x = 10
⇔ x2 + 9x - 10 = 0
⇔ x2 - x + 10x - 10 = 0
⇔ x( x - 1 ) + 10( x - 1 ) = 0
⇔ ( x - 1 )( x + 10 ) = 0
⇔ x - 1 = 0 hoặc x + 10 = 0
⇔ x = 1 hoặc x = -10
4. 2x2 + 9x = 35
⇔ 2x2 + 9x - 35 = 0
⇔ 2x2 + 14x - 5x - 35 = 0
⇔ 2x( x + 7 ) - 5( x + 7 ) = 0
⇔ ( x + 7 )( 2x - 5 ) = 0
⇔ x + 7 = 0 hoặc 2x - 5 = 0
⇔ x = -7 hoặc x = 5/2
5. ( x2 - 2x - 1 )2 - 5( x2 - 2x - 1 ) - 14 = 0
Đặt t = x2 - 2x - 1
bthuc ⇔ t2 - 5t - 14 = 0
⇔ t2 - 7t + 2t - 14 = 0
⇔ t( t - 7 ) + 2( t - 7 ) = 0
⇔ ( t - 7 )( t + 2 ) = 0
⇔ ( x2 - 2x - 1 - 7 )( x2 - 2x - 1 + 2 ) = 0
⇔ ( x2 - 4x + 2x - 8 )( x - 1 )2 = 0
⇔ ( x - 4 )( x + 2 )( x - 1 )2 = 0
⇔ x - 4 = 0 hoặc x + 2 = 0 hoặc x - 1 = 0
⇔ x = 4 hoặc x = -2 hoặc x = 1
6. ( 2k2 + 5k + 1 )2 - 12( 2k2 + 5k + 1 ) + 32 = 0
Đặt t = 2k2 + 5k + 1
bthuc ⇔ t2 - 12t + 32 = 0
⇔ t2 - 8t - 4t + 32 = 0
⇔ t( t - 8 ) - 4( t - 8 ) = 0
⇔ ( t - 8 )( t - 4 ) = 0
⇔ ( 2k2 + 5k + 1 - 8 )( 2k2 + 5k + 1 - 4 ) = 0
⇔ ( 2k2 - 2k + 7k - 7 )( 2k2 - k + 6k - 3 ) = 0
⇔ ( k - 1 )( 2k + 7 )( 2k - 1 )( k + 3 ) = 0
⇔ k = 1 hoặc k = -7/2 hoặc k = 1/2 hoặc k = -3